Bisikan atau Suara Lantang: Perjalanan Advokasi Kebijakan Larangan Penggunaan Plastik Sekali-Pakai Melalui Partisipasi Pemuda di Provinsi DKI Jakarta dan Bali - Lestari, Binar Asri; Ragamustari, Safendrri Komara; Hirawan, Fajar Bambang (Universitas Gadjah Mada, 2023)
Policy making in a democratic country must be inclusive—involving the participation of various segments of society, youth is no exception to be left behind. The attempt made by the public to influence this process is called policy advocacy. There are various problems in this country that require policy advocacy, one of which is the climate crisis. Since the problem is quite complex and has many sub-facets, the climate crisis needs a serious policy instrument from the government. One of the issues that is closely related to the climate crisis is the use of single-use plastic bags. This study aims to look at youth participation in policy advocacy related to the ban on the single-use plastic bags in DKI Jakarta and Bali Provinces. Using a qualitative approach, this study compares youth organizations that carry out policy advocacy in each province—namely Gerakan Indonesia Diet Kantong Plastik (GIDKP) in DKI Jakarta and Bye Bye Plastics Bag (BBPB) in Bali. Based on Hart’s ladder of youth participation, it appears that youth participation in GIDKP’s campaign activities is at level 6 (adult-inisiated shared decisions with youth) while BBPB’s is already at level 8 (youth-initiated shared decisions with adults)—but only reaches level 3 (tokenism) for direct government lobbying. Thus, based on Gen and Wright’s framework of policy advocacy strategies , it can be concluded that GIDKP carries out direct reform strategy whilst BBPB tends to use popular power strategy. There needs to be a collaboration between both organization’s specific strategies and competencies to achieve their mutual policy advocacy goal.